Speech at the 2017 Annual Meetings Plenary - Kim, Jim Yong (World Bank, Washington, DC, 2019)
Jim Yong Kim, President of the World Bank Group, discussed the following topics: 1) actions needed to grow the economies and compete in what will be a more complex, demanding, and digitized future; 2) three ways to end extreme poverty by 2030, and boost shared prosperity among the poorest 40 percent around the world: a) accelerating inclusive, sustainable economic growth, b) building resilience to shocks and threats, and c) investing more and more effectively in people.